Answer:
![F(x)=(x-11)(x-3)](https://img.qammunity.org/2020/formulas/mathematics/college/gzl8j12jofjvy5wwjmx4gah94ty0xeift5.png)
Explanation:
we have
![F(x)=x^(2) -14x+33](https://img.qammunity.org/2020/formulas/mathematics/college/oozvfs8riy3rz6hyaheuq6oeqxkz0c262p.png)
Find the zeros of the function
F(x)=0
![0=x^(2) -14x+33](https://img.qammunity.org/2020/formulas/mathematics/college/b5brs0srpyl73te6gwfl0lipr1hsqf54a3.png)
Group terms that contain the same variable, and move the constant to the opposite side of the equation
![-33=x^(2) -14x](https://img.qammunity.org/2020/formulas/mathematics/college/ryrulgjf49oggfmkqkpzw75scckncdh1id.png)
Complete the square. Remember to balance the equation by adding the same constants to each side
![-33+49=x^(2) -14x+49](https://img.qammunity.org/2020/formulas/mathematics/college/x7ifkj4ptjljmyfle1z4j9ck0w4vchyjtz.png)
![16=x^(2) -14x+49](https://img.qammunity.org/2020/formulas/mathematics/college/kd49dvy6xg4g3oczcl0w32oppm669geqc0.png)
Rewrite as perfect squares
![16=(x-7)^(2)](https://img.qammunity.org/2020/formulas/mathematics/college/s7y4rnkteiuc55xyuyfeoxiixs8pausaml.png)
square root both sides
![(x-7)=(+/-)4](https://img.qammunity.org/2020/formulas/mathematics/college/yqvxh6srrovk8t70e80vp5mbdbqnazwfw7.png)
![x=(+/-)4+7](https://img.qammunity.org/2020/formulas/mathematics/college/38ooexe0bb32gab7i6juzvzvfcq308at02.png)
![x=(+)4+7=11](https://img.qammunity.org/2020/formulas/mathematics/college/3e3w56r0ur05kwiu5sllziq1hjn4z4bhk4.png)
![x=(-)4+7=3](https://img.qammunity.org/2020/formulas/mathematics/college/kqzx47edhku3ielwsv2slmaqeyyd9xxbfl.png)
so
The factors are
(x-11) and (x-3)
therefore
![F(x)=(x-11)(x-3)](https://img.qammunity.org/2020/formulas/mathematics/college/gzl8j12jofjvy5wwjmx4gah94ty0xeift5.png)